Pengaruh Persepsi Toleransi, Wawasan Kebangsaan terhadap Radikalisme di Kalangan Mahasiswa - Justicia Chantika; Putu Isma Saraswati; Syilfa Fakhira; Yassar Hasan; Catur Nugroho (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
The purpose of this study was to determine whether or not there is an influence of perceptions of tolerance, national insight on radicalism among students in Indonesia. This research method uses quantitative methods with data analysis techniques using the classical assumption test. The data collection technique was carried out by distributing questionnaires, while the population in this study were active students with a sample of 100 students spread across several cities, namely Padang, Purwokerto, Bali and Majalengka. The results of this study indicate that the data of multiple linear regression analysis on the F test which shows a significance value for the effect of X1 and X2 simultaneously on Y is 0.00 <0.05 and the calculated F value is 13.594 > 3.09 so it can be concluded that H3 is accepted means that there is an effect of X1 and X2 simultaneously on Y. And the results of the coefficient of determination show that perceptions of tolerance, nationalism have an influence of 21% on radicalism. The conclusions of the research show that there is an influence of perceptions of tolerance, nationalism towards radicalism among Indonesian student Keywords: National Insight, Radicalism, Tolerance, Quantitative